MATH ANXIETY SISWA: LEVEL DAN ASPEK KECEMASAN SERTA PENYEBABNYA - Mardhatillatus Sholichah, Fazha; Aini, Afifah Nur (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2022)
Math anxiety is a student's anxiety when learning mathematics. This research is qualitative descriptive to describe the levels and aspects of students' math anxiety and its causes. The research subjects were class VIII students of MTs Bustanul Ulum Krai who were selected by purposive sampling method. The instruments used were questionnaires and interviews. The results showed that 96% of students had moderate levels of math anxiety and the rest had low cognitive aspects, while the affective and physiological aspects had moderate levels of student math anxiety. The reason is the low self-confidence of students and a lack of mathematical ability.